Development of Gel Preparations from a Combination of Iler Leaf Extract and Patchouli Oil as a Repellent Against Aedes aegypti Mosquitoes - Wahyuni, Ayu Nuki; Anny Victor Purba; Ratna Djamil (Journal of Natural Product for Degenerative Diseases, 2023)
Dengue Hemorrhagic Fever (DHF) is an abnormal health condition caused by the dengue virus through the bite of the Aedes aegypti mosquito. The use of repellent to prevent mosquito bites can provide protection against DHF. DEET, a synthetic repellent with usage that has spread throughout the world, is reported to have toxic effects and cause irritation. Leaves of iler and patchouli oil are plants of the Lamiaceae family with repellent activity. This study aimed to obtain a repellant gel combination of iler leaf extract and patchouli oil. Gel preparations are made with a combination of Iler Leaf Extract and Patchouli Oil at concentrations of 12.5%, and 2%. Physical and chemical quality parameter test, stability test, acute dermal irritation test, and repel effectiveness test were tested on Aedes aegypti mosquitoes. Gel preparations showed a homogeneous physical appearance, greenish-brown color with an aromatic distinctive odor, a viscosity value of 16000 cPs, pH 6.32, and thixotropic flow properties. Gel preparations are effective as a mosquito repellent for 3 hours with a protection power of 56.82%. The gel preparation storage temperature, besides the resulting gel, does not irritate, and it is physically stable at 4 ± 2oC and 25 ± 2oC and is slightly less stable at 40 ± 2oC.